Steroid hormone regulation of immunometabolism and inflammation - Smith, Ley Cody; Ramar, Mohankumar; Riley, Gregory L.; Mathias, Clinton B.; Lee, Ji-Young (Frontiers in Immunology, 2025)
The metabolism of immune cells adapts to support the energy demands for their activation, differentiation, and effector functions through a process known as metabolic reprogramming. This metabolic plasticity is influenced by both extrinsic and intrinsic factors, including steroid hormones such as glucocorticoids, androgens, progestogens, and estrogens. These critical mediators modulate immune function and inflammatory responses through genomic and non-genomic regulation of intracellular metabolic pathways, including glycolysis, the tricarboxylic acid cycle, and oxidative phosphorylation. Interestingly, these effects appear to be dependent on cell type, hormonal concentration, and microenvironmental context. Herein, we discuss how steroid hormones regulate inflammation and immunometabolism and summarize recent studies highlighting immunometabolic regulation by steroid hormones as the key driver of their immunomodulatory effects. We also address potential mechanisms contributing to their seemingly dichotomous and context-specific regulation. Understanding the link between steroid hormone signaling, immunometabolism, host defense, chronic inflammation, and immunity will expand our understanding about how biological sex and stress influence the immune system and facilitate more precise therapeutic targeting of immune cell activity to mitigate inflammation- and immune-mediated diseases.